2023
DOI: 10.1038/s12276-023-01028-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulation through tryptophan metabolism

Abstract: Amino acids are fundamental units of molecular components that are essential for sustaining life; however, their metabolism is closely interconnected to the control systems of cell function. Tryptophan (Trp) is an essential amino acid catabolized by complex metabolic pathways. Several of the resulting Trp metabolites are bioactive and play central roles in physiology and pathophysiology. Additionally, various physiological functions of Trp metabolites are mutually regulated by the gut microbiota and intestine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…One of these pathways is involved in L-tryptophan biosynthesis. Tryptophan is the precursor to serotonin, a key neurotransmitter implicated in mood and typically targeted by antidepressants − which, unlike serotonin, can cross the blood−brain barrier to the central nervous system and plays a role in modulation of both peripheral and central neuroinflammatory responses ( Mithaiwala et al, 2021 ; Seo and Kwon, 2023 ). This finding is consistent with a previous study that found socio-economic risk in children to be associated with microbiome functional pathways of monoamine metabolism, including a tryptophan metabolism pathway.…”
Section: Discussionmentioning
confidence: 99%
“…One of these pathways is involved in L-tryptophan biosynthesis. Tryptophan is the precursor to serotonin, a key neurotransmitter implicated in mood and typically targeted by antidepressants − which, unlike serotonin, can cross the blood−brain barrier to the central nervous system and plays a role in modulation of both peripheral and central neuroinflammatory responses ( Mithaiwala et al, 2021 ; Seo and Kwon, 2023 ). This finding is consistent with a previous study that found socio-economic risk in children to be associated with microbiome functional pathways of monoamine metabolism, including a tryptophan metabolism pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A primary and well-established function of KP activation is immune system suppression, largely mediated by cytokine-induced IDO expression. 372 This manifests in diminished proliferation and inactivation of immune cells, including T and NK cells. 212 , 233 , 371 , 373 Simultaneously, the activation boosts the generation of vital bioactive KP metabolites, culminating in the metabolically-indispensable cofactor NAD.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in certain cancers, it creates an environment that supports tumour expansion. 372 Prolonged activation of the KP may also elevate levels of several KP metabolites, some of which are known to have deleterious effects. Neurotoxic QUIN, for instance, which could play a role in advancing several CNS and periphery diseases by generating reactive oxygen species and functioning as both as an excitotoxin at NMDA receptors, and perturbing synaptic glutamate uptake and recycling.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, when IDO activity increases, more tryptophan is diverted away from serotonin synthesis and toward kynurenine. Interestingly, the aryl hydrocarbon receptor (AhR) of the tryptophan-kynurenine pathway serves as a critically important mediator between tryptophan metabolism, immune reactions, and tissue homeostasis ( 41 43 ), and several kynurenine metabolites have been associated with fatigue ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%